Free water effect on the dynamic compressive properties of mortar - Zhang, Xihong; Chiu, Yu-wen; Hao, Hong; Cui, Jian (Elsevier, 2021)
This paper investigates the effect of free water on the dynamic compressive properties of mortar. Total-dried and full-saturated specimens are prepared through oven drying and water soaking processes. Common and high-porosity mortars are studied to examine the influence of porosity. Compression tests are carried out, covering strain rates between 1 × 10−6/s and 280/s. The test results show both dry and saturated mortar specimens are strain-rate sensitive. Free water results in softening effect in both common and high-porosity mortars at quasi-static and dynamic states. Retarding effect by pore water in the mortar is observed, which leads to lower longitudinal wave velocities in the saturated specimens. Water saturation increases the hydrostatic-pressure and leads to more severe water bursting; consequentially reduces the compressive strength. The experimental results demonstrate the free water deteriorates the compressive properties of mortars as a result of hydric expansion, which induces new cracks, especially in the high-porosity mortar.